Disentangling the relationship between corruption and shadow economy - Rais, Jonáš; Rod, Aleš; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
This paper analyses the relationship between corruption and shadow economy. Synthesis of existing theoretical models and the empirical findings in this paper show that different types of corrupt behavior interact with shadow economy differently. Therefore, the relationship between contexts differs. Overall, it seems that the mechanisms leading to the complementary relationship are more prevalent. The results also imply that the quality of public goods available in the official economy influences where the different types of corrupt behavior manifest. When the quality of the public goods is high, corruption and shadow economy appear to be substitutes and when the quality is low, they are complements. However, the relationship is not robust and depends upon the measures used to assess the public goods quality. Furthermore, corruption and shadow economy seem to be complements in decentralized countries and countries with high taxes.
Vedoucí práce: Aleš Rod
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses